Development of Integrated Electrocoagulation-Sedimentation (IECS) in Continuous Mode for Turbidity and Color Removal - Saret Bun; Penghour Hong; Nattawin Chawaloesphosiya; Sreynich Pang; Sreyla Vet; Phaly Ham; Rathborey Chan; Pisut Painmanakul (ChemEngineering, 2022)
The present work focused on the development and evaluation of a compact electrocoagulation (EC) reactor, combined between EC and clarifier processes in continuous modes for decolorization and turbidity removal, named the integrated electrocoagulation-sedimentation reactor (IECS). The experiments were firstly conducted in the four-liter batch column in order to optimize the EC configuration and operation condition. The removal kinetics were also investigated and predicted for kinetic correlations. After various optimization steps, the IECS reactor was conducted, consisting of EC and clarifier compartments. Liquid flow pattern in EC compartment was examined through resident time distribution technique for defining the number of EC units and divided baffles. In summary, four units of EC were placed in the EC compartment of the IECS reactor with 90% in the width of three baffles. Each EC unit had two pairs of aluminum electrode plats in monopolar arrangement with a 1.5 cm gap and required a current density of 13.5 mA/cm2. For the clarifier compartment, it was mainly designed based on the batch settling test for separating the precipitated particles. The treatment performance of the IECS reactor was tested at different liquid flows in order to reduce the pollutant to a certain level. For the individual condition, liquid flow rates of 3 and 1 L/min were defined for turbidity and color, respectively. If both pollutants are presented simultaneously, a liquid flow rate of 1–2 L/min can be used for decreasing turbidity from 250 to <20 NTU and color from 6000 to <300 ADMI.